Auditory Brainstem Response (ABR) Abnormalities across the Life Span of Rats Prenatally Exposed to Alcohol - Church, Michael W. (2011)
BACKGROUND: Fetal Alcohol Syndrome is a leading cause of neurodevelopmental impairments (NDI) in developed countries. Sensory deficits can play a major role in NDI, yet few studies have investigated the effects of prenatal alcohol exposure on sensory function. In addition, there is a paucity of information on the life-long effects of prenatal alcohol exposure. Thus, we sought to investigate the effects of prenatal alcohol exposure on auditory function across the life span in an animal model. Based on prior findings with prenatal alcohol exposure and other forms of adverse prenatal environments, we hypothesized that animals prenatally exposed to alcohol would show an age-dependent pattern of (A) hearing and neurological abnormalities as post-weanling pups, (B) a substantial dissipation of such abnormalities in young adulthood, and (C) a resurgence of such abnormalities in middle-aged adulthood. METHOD: Pregnant rats were randomly assigned to an untreated control (CON), a pair-fed control (PFC) or an alcohol treated group (ALC). The ALC dams were gavaged with 6 mg/kg alcohol daily from gestation day (GD) 6 to 21. The PFC dams were gavaged daily from GD6-21 with an isocaloric and isovolumetric water-based solution of Maltose-Dextrins and pair-fed to the ALC dams. The CON dams were the untreated group to which the ALC and CON groups were compared. Hearing and neurological functions in the offspring were assessed with the Auditory Brainstem Response (ABR) at the postnatal ages of 22, 220 and 520 days of age. RESULTS & CONCLUSIONS: In accord with our hypothesis, ABR abnormalities were first observed in the post-weanling pups, largely dissipated in young adulthood, and then resurged in middle-aged adulthood. This age-related pattern suggests that the ALC pups had a developmental delay that dissipated in young adulthood and an enhanced age-related deterioration that occurred in middle-aged adulthood. Such a pattern is consistent with the fetal programming hypothesis of adult-onset diseases (the Barker Hypothesis). Our findings have important clinical implications for the assessment and management of (A) childhood hearing disorders and their co-morbidities (i.e., speech-and-language, learning, and attention deficit disorders) and (B) enhanced age-related hearing and neurological degeneration in middle-aged adulthood that can result from prenatal alcohol exposure. We recommend hearing evaluation be a part of any long-term follow-up for FAS patients and patients exposed to any adverse prenatal environment.